THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT AND THE CHARACTERISTICS OF THE WORK OF THE EMPLOYEE PERFORMANCE : MOTIVATION AS MEDIATION VARIABLE PT.INDOSAT - Windu Samodra (Business and Entrepreneurial Review, 2014)
The background of this research is the need to manage human resources in order to improve its performance in achieving the objectives of the company. PT. Indosat as a telecommunications operator in Indonesia experiences the challenge to improve the performance of its employees. Earlier research showed that the perceived organizational support and job characteristics other than can affect performance, it can also affect employee motivation. Where is the motivation of the employees can also improve the performance of employees?The purpose of this study was to analysis the influence of perceived organizational support and job characteristics on performance of employee directly or by mediation the motivation.The design of this research is applied to PT. Indosat with the descriptive hypothesis testing method to test the relationships between variables. Data collection is done by a questionnaire that was given to the respondent.Data analysis conducted in this research is descriptive statistics, inferential analysis and Structural Equation Modeling (SEM).The result of this research indicate proven his market timing hypothesis put forward in the fifth study,  i.e. perceived organizational support a positive and significant effect on performance, perceived organizational support  of influential positive and significant of motivation, job characteristics, positive and significant effect on performance , job characteristics positive and significant effect on  motivation, motivation and a positive and significant effect on performance. While the perceived organizational support and relationships characteristic of employment directly against the stronger performance through motivation.